The Relationship between Pre-Pandemic Interferon Gamma Release Assay Test Results and COVID-19 Infection: Potential Prognostic Value of Indeterminate IFN-γ Release Assay Results. (5th August 2021) - Borekci, Sermin; Karakas, Fatma Gulsum; Sirekbasan, Serhat; Kubat, Bahar; Karaali, Rıdvan; Can, Gunay; Kocazeybek, Bekir Sami; Gemicioglu, Bilun
Abstract : Objective . To reveal the relationship between interferon-gamma release assay (IGRA) test (Standard ETB-Feron ELISA (TBF)) results performed within 12 months before the COVID-19 pandemic and the frequency of COVID-19 infections and the severity of COVID-19. Methods . The retrospective TBF test results and contact information of 684 patients aged over 18 years who underwent TBF testing between March 11th, 2019, and March 10th, 2020, were obtained. Of the 684 patients contacted by phone, 365 agreed to participate in the study and were enrolled. The patients were divided into three groups (TBF test positive, negative, and indeterminate). The data obtained from the questionnaire were compared statistically. Results . According to the TBF test results, positive ( n  = 51, 14%), negative ( n  = 286, 78.3%), and indeterminate ( n  = 28, 7.7%) groups were compared. The frequency of COVID-19 infections in the indeterminate group was found significantly higher than that in the positive and negative groups (p = 0.005 ). When the group with COVID-19 ( n  = 46, 12.6%) was compared with the group without ( n  = 319, 87.4%), no difference was found in terms of age, sex, body mass index, smoking history and number of cigarettes smoked, TB history, diabetes mellitus, hypertension, coronary artery disease, and biologic and corticosteroid therapy use. Only the frequency of obstructive pulmonary disease was significantly higher in the group without COVID-19 (p = 0.033 ). Conclusion . The frequency of COVID-19 infection was increased in patients with indeterminate TBF test results. Indeterminate TBF test results may be a guide in terms of risk stratification in groups at risk for COVID-19.